Outstanding Humidity Chemiresistors Based on Imine-Linked Covalent Organic Framework Films for Human Respiration Monitoring - Chen, Xiyu; Kong, Lingwei; Mehrez, Jaafar Abdul‑Aziz; Fan, Chao; Quan, Wenjing; Zhang, Yongwei; Zeng, Min; Yang, Jianhua; Hu, Nantao; Su, Yanjie; Wei, Hao; Yang, Zhi (Nano-Micro Letters, 2023)
Human metabolite moisture detection is important in health monitoring and non-invasive diagnosis. However, ultra-sensitive quantitative extraction of respiration information in real-time remains a great challenge. Herein, chemiresistors based on imine-linked covalent organic framework (COF) films with dual-active sites are fabricated to address this issue, which demonstrates an amplified humidity-sensing signal performance. By regulation of monomers and functional groups, these COF films can be pre-engineered to achieve high response, wide detection range, fast response, and recovery time. Under the condition of relative humidity ranging from 13 to 98%, the COFTAPB-DHTA film-based humidity sensor exhibits outstanding humidity sensing performance with an expanded response value of 390 times. Furthermore, the response values of the COF film-based sensor are highly linear to the relative humidity in the range below 60%, reflecting a quantitative sensing mechanism at the molecular level. Based on the dual-site adsorption of the (–C=N–) and (C–N) stretching vibrations, the reversible tautomerism induced by hydrogen bonding with water molecules is demonstrated to be the main intrinsic mechanism for this effective humidity detection. In addition, the synthesized COF films can be further exploited to effectively detect human nasal and oral breathing as well as fabric permeability, which will inspire novel designs for effective humidity-detection devices. Highlights: 1 Imine groups in covalent organic framework (COF) films act as dual-active sites for humidity sensing, inducing an intrinsic enhanced mechanism of reversible protonated tautomerism via water molecule-induced hydrogen bonding. 2 The cis-ketoimine reciprocal isomerization induces a stretching vibration effect for the ordered conjugated conductive frame of COF films, realizing fast response, wide range, and high sensitivity characteristics for humidity detection. 3 Resistance changes of COF film-based sensors keep a strong linear relationship with low-range relative humidity, reflecting the quantitative sensing mechanism at the molecular level.